Impact of MGNREGA on Rural Poor: A Case Study of Panchrukhi Block, District- Kangra, Himachal Pradesh - Swarup, Guru; Tiwar, Jitender Kumar (Journal of Management and Science, 2013)
Indian economy is growing at rapid pace but more than one fourth of rural population found to be below poverty line due to fluctuations in employment, shrinking employment opportunities, and low wage rates. Government of India (GoI) has been introducing a number of wage employment programmes. The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is among one of them. The Indian Parliament has passed MGNREGA act in 2005, which came into force in February 2006. MGNREGA evidently indicate increase in employment opportunities, and market wage rates and reduction in distress migration in many parts of the country. This paper is an attempt to study the impact of MGNREGA on the life style of rural poor. The study is confined to 6 panchayats Shimbal khola, Tikker, Tatehal, Biara, Ladoh and Rajot of Panchrukhi block, District Kangra, H.P. The study is based on both primary and secondary data. The main findings of the study are most of the people think that MGNREGA is helpful in the development of the village, most of the people are not aware about the process and practices under MGNREGA Scheme, most of the people are not aware of how much money is coming from the block level and how much is used in the public works, most of the people think that the earning in terms of wages through MGNREGA is helping in the financial upliftment of the life styles of the people. As far as corruption is concerned in MNREGA people are almost of the same opinion. People are of the mixed opinion that corruption exists in MGNREGA as well as there is no point of corruption in MGNREGA.